Environmental intervention in a university canteen with focus on decision guidance : an evaluation study regarding food consumption, nutrient intake, perception, and satisfaction by canteen users - Melanie Schneider; Carolin Nössler; Anja Carlsohn; Petra Maria Lührmann (Journal of public health research, 2023)
Background: An environmental intervention with focus on Decision Guidance was implemented in a university canteen. It comprised the offer of a health promoting food option (HPFO), including a health promoting lunch option and health promoting snacks. Design and methods: Possible changes of food consumption and nutrient intake of student canteen users (substudy A), perception of the HPFO by canteen users (substudy B.1), and possible changes of their satisfaction regarding the canteen (substudy B.2) at least 10 weeks after the start of the intervention were examined. Substudy A used a controlled pretest-posttest-design (paired sample). The students were assigned to intervention group (canteen visits ≥ once/week, n = 27) or control group (canteen visits < once/week, n = 39). Substudy B.1 used a cross-sectional design, and substudy B.2 a pretest-posttest-design (paired sample). Only canteen users (≥once/week) were included (substudy B.1 n = 89, substudy B.2 n = 30). Results: Food consumption and nutrient intake did not change (p > 0.05) in the intervention group versus control group (substudy A). In substudy B.1 canteen users were aware of the HPFO, appreciated it highly, and were satisfied with it. In substudy B.2 canteen users were at posttest more satisfied regarding service and health value of offered lunches (p < 0.05). Conclusions: Although the HPFO was positively percepted, no effects on the daily diet were observed. The offered proportion of the HPFO should be increased.
Keywords: decision guidance; Environmental intervention; food consumption; nutrient intake; university canteen; university students